2018
DOI: 10.1038/s41541-018-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

Down-selection of the VAR2CSA DBL1-2 expressed in E. coli as a lead antigen for placental malaria vaccine development

Abstract: Over 50 million women are exposed to the risk of malaria during pregnancy every year. Malaria during pregnancy is a leading global cause of maternal morbidity and adverse pregnancy outcomes. Adhesion of Plasmodium falciparum-infected erythrocytes to placental chondroitin-4-sulfate (CSA) has been linked to the severe disease outcome of placental malaria. Accumulated evidence strongly supports VAR2CSA as the leading placental malaria vaccine candidate. Recombinant proteins encompassing the VAR2CSA high affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 32 publications
(49 reference statements)
3
33
1
Order By: Relevance
“…The design of the non-clinical toxicology study was performed according to the “Guidelines on the non-clinical evaluation of vaccine adjuvants and adjuvanted vaccines” [27]. Rats were chosen as it is a rodent species in which an immune response to the vaccine antigen VAR2CSA is developed and enhanced by the adjuvants Alhydrogel® and GLA-SE [24] through mechanisms expected to be similar than in humans. Three groups of 15 male and 15 female Sprague-Dawley rats received the vaccine candidate, PRIMVAC, at the dose-level of 110 μg/animal, alone (group 3) or adjuvanted with either Alhydrogel® (Brenntag, Denmark) at 0.85 mg/animal (group 4) or GLA-SE (Infectious Disease Research Institute, USA) at 5 μg/animal (group 5), by intramuscular injection, on Days 1, 15, 29 and 43.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The design of the non-clinical toxicology study was performed according to the “Guidelines on the non-clinical evaluation of vaccine adjuvants and adjuvanted vaccines” [27]. Rats were chosen as it is a rodent species in which an immune response to the vaccine antigen VAR2CSA is developed and enhanced by the adjuvants Alhydrogel® and GLA-SE [24] through mechanisms expected to be similar than in humans. Three groups of 15 male and 15 female Sprague-Dawley rats received the vaccine candidate, PRIMVAC, at the dose-level of 110 μg/animal, alone (group 3) or adjuvanted with either Alhydrogel® (Brenntag, Denmark) at 0.85 mg/animal (group 4) or GLA-SE (Infectious Disease Research Institute, USA) at 5 μg/animal (group 5), by intramuscular injection, on Days 1, 15, 29 and 43.…”
Section: Methodsmentioning
confidence: 99%
“…Var2csa orthologues are conserved among parasite isolates and strains but the relatively high degree of protein sequence polymorphisms represents a challenge for vaccine design [20]. Nevertheless, several studies demonstrated that immunoglobulins from anti-sera raised against VAR2CSA recombinant proteins were able to recognize IEs from placental origins but also to block their adhesion to CSA [[21], [22], [23], [24]]. Taken together these studies suggest that VAR2CSA expressed by placental parasites possesses conserved antigenic determinants that are the target of antibodies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this binding is responsible for the blood supply to the placenta, at the same time it increases the risk of babies with low birth weight. Currently, the research is focused on the development of a vaccine against conserved regions of the PfEMP protein in order to reduce Malaria in Sub Saharan Africa (66).…”
Section: Pregnancy-associated Malaria Vaccinesmentioning
confidence: 99%